Ratio of Placenta to Birth Weight in Anemic and Non-Anemic Mothers - Khatun, Sanzida; Shah, Diwakar Kumar; Shrestha, Nischal; Yadav, Ashis Kumar (Journal of Nobel Medical College, 2022)
Background: The placenta is a uterine organ in pregnancy which facilitates exchange of materials between maternal and fetal circulation. Decreased maternal hemoglobin decreases oxygen supplementation to fetus among anemic mothers which may cause low birth weight. The aim of this study was to compare the ratio of placenta to birth weight among anemic and non-anemic mothers. Materials and Methods: A comparative cross-sectional study was conducted in 82 anemic pregnancies and 203 non-anemic pregnancies in Department of Obstetrics & Gynecology, Nobel Medical College Teaching Hospital, Biratnagar. Participants with haemoglobin concentration lower than 11 g/dl were included in anemic group and 11g/dl or more in non-anemic group. The difference of means of placental weight, birth weight and placenta to birth weight ratio in anemic and non-anemic groups was determined by Student’s t-test. Results: In anemic group, mean placental weight was 578.78±141.80 g, mean birth weight was 2973.17±680.97 g and mean placenta to birth weight ratio was 0.20±0.05. In non-anemic group, mean placental weight was 575.96±128.88 g, mean birth weight was 3125.91±590.89 g and mean placenta to birth weight ratio was 0.19±0.05. Significant difference was observed in means of placenta to birth ratio in anemic and non-anemic groups (p-value 0.05). Conclusion: Mean placental weight and mean ratio of placenta to birth weight was higher in pregnant women with anemia than in non-anemic pregnant women and significant difference was observed in means of placenta to birth ratio between anemic and non-anemic groups.